Experimental study on the beneficiation of low-grade iron ore fines using hydrocyclone desliming, reduction roasting and magnetic separation. (December 2014) - Suthers, Steven Paul; Nunna, Venkata; Tripathi, Avinash; Douglas, Jeffrey; Hapugoda, Sarath
<x content-type="archive" xml:space="preserve">Abstract</x> Beneficiation of −2 mm low-grade iron ore tailings (50·7%Fe, 10·8%SiO2 and 4·4%Al2O3) from Western Australia was studied. The sample consisted of hydrohaematite, goethite and quartz, with lesser kaolinite and shale. Two processing options were tested, which were wet high-intensity magnetic separation (WHIMS), either using deslimed or untreated feed, and reduction (magnetising) roasting of deslimed feed followed by Davis tube tests (DTT). WHIMS tests using deslimed feed gave a product having 55·4%Fe, 6·1%SiO2 and 2·7%Al2O3, while the iron recovery was 55·7%. The calcined iron grade was 62·1%Fe. Davis tube tests using deslimed feed that had been reduction roasted at 700°C using a 1∶1 mixture of CO/CO2 gave a product with 63·2%Fe, 5·4%SiO2 and 2·9%Al2O3, while the iron recovery was 60·1%. Overall, desliming followed by reduction roasting and DTT produced the highest grade product with the highest iron recovery.